Breaking Down Anonymity Digital Surveillance of Irregular Migrants in Germany and the Netherlands - Broeders, Dennis (IMISCoe Dissertations, 2009)
Because borders alone cannot stop irregular migration, the European Union is turning more and more to internal control measures. Through surveillance, member states aim to exclude irregular migrants from societal institutions, thereby discouraging their stay or deporting those who are apprehended. And yet, states cannot expel immigrants who remain anonymous. Identification has thus become key. Breaking Down Anonymity shows how digital surveillance is becoming a prime instrument of identification and exclusion policies towards irregular migrants. To support this claim, the study charts policy developments in Germany and the Netherlands. It analyses both countries' labour market controls as well as their detention and expulsion practices. Also examined is the development of several new EU migration databases. Spanning the Continent, these information systems create a new European Union frontier - one that is digital, biometric and ever-strengthening.